2004
DOI: 10.1177/002215540405201002
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Localization of Ornithine Decarboxylase and Its Regulatory Protein, Antizyme-1

Abstract: The enzyme ornithine decarboxylase (ODC) and its regulatory protein antizyme-1 (AZ1) are key regulators in the homeostasis of polyamines. To gain more insight into the exact intracellular distribution of ODC and AZ1, we performed immunocytochemical and Green Fluorescent Protein-fluorocytochemical studies in cultured human cervix carcinoma and human prostatic carcinoma (PC-346C) cells. ODC localization patterns varied from predominantly cytoplasmic to both cytoplasmic and nuclear staining, whereas AZ1 was mostl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 20 publications
1
10
2
Order By: Relevance
“…The previous report showed that AZ1 is primarily localized in the nucleus where it transports ODC from the cytosol for degradation by nuclear proteasome (Gritli-Linde et al 2001, Murai et al 2003, Schipper et al 2004. By contrast, we found that AZ1 was mainly localized in the cytosol during conversion of AsPC-1 cells to the differentiated state (Fig.…”
Section: J-i Suzuki Et Al: Glucagon-producing Cell Differentiationcontrasting
confidence: 45%
“…The previous report showed that AZ1 is primarily localized in the nucleus where it transports ODC from the cytosol for degradation by nuclear proteasome (Gritli-Linde et al 2001, Murai et al 2003, Schipper et al 2004. By contrast, we found that AZ1 was mainly localized in the cytosol during conversion of AsPC-1 cells to the differentiated state (Fig.…”
Section: J-i Suzuki Et Al: Glucagon-producing Cell Differentiationcontrasting
confidence: 45%
“…Antizyme-1 was found in the nucleus co-localized with ODC after treatment of carcinoma cells with polyamines or polyamine analogs (41). It was suggested on the basis of these experiments, which utilized an ODC fused to green fluorescent protein, that antizyme may be involved in nucleocytoplasmic shuttling of ODC (41). Antizyme and ODC accumulated in the nucleus after treatment with a proteasome inhibitor (40), which would also be consistent with a nuclear degradation of ODC.…”
Section: Multiple Forms Of Antizymementioning
confidence: 75%
“…Translocation of antizyme-1 to the nucleus occurs during mouse development (40). Antizyme-1 was found in the nucleus co-localized with ODC after treatment of carcinoma cells with polyamines or polyamine analogs (41). It was suggested on the basis of these experiments, which utilized an ODC fused to green fluorescent protein, that antizyme may be involved in nucleocytoplasmic shuttling of ODC (41).…”
Section: Multiple Forms Of Antizymementioning
confidence: 99%
“…To our knowledge, this is the first report which has investigated the use of atypical subcellular targeting for this purpose. The native compartment for ODC is the cytosol, although some ODC also accumulates in the nucleus [34][35][36][37][38][39]. ODC enzyme activity has also been detected in isolated mitochondria and chloroplasts [40].…”
Section: Discussionmentioning
confidence: 99%